Long-term Satisfaction with CO2 Laser Treatment for Moderate to Major Rhinophyma: A Single-centre Study - Berta Olafsdottir; William Jebril; Philip Curman; Etty Bachar-Wikström; Jakob D. Wikström (Acta Dermato-Venereologica)
Rhinophyma, a severe manifestation of rosacea, predominantly affects Caucasian males aged 50–70 and is characterized by thickening and enlargement of the nasal skin. The condition can seriously both impact cosmetic appearance and obstruct nasal breathing. While its appearance is distinct, conditions such as basal cell carcinoma can mimic it, complicating diagnosis. Treatment options for rhinophyma range from medical therapies to surgical interventions, with CO2 laser resurfacing emerging as the gold standard due to its precision and minimal blood loss. This retrospective case series evaluates the long-term efficacy and patient satisfaction of CO2 laser treatment in 11 male patients treated between 2015 and 2023 at the Karolinska University Hospital. The results revealed sustained positive outcomes, with 92% of patients reporting high satisfaction and 55% experiencing improved nasal airflow post-procedure. Despite some instances of hypopigmentation and scarring, no major side effects were reported. The study supports CO2 laser treatment as a safe and effective option for moderate to major rhinophyma in Caucasian male patients with Fitzpatrick skin types I–III. The importance of considering skin type, where extra caution must be employed when treating skin types IV–VI, should be emphasized as the treatment